Postoperative myocardial infarction in lung cancer patients with: incidence rate, clinical features, prognostic factors - O. A. Bolshedvorskaya; K. V. Protasov; P. S. Ulybin; V. V. Dvornichenko (Российский кардиологический журнал, 2020)
Aim. To study the incidence, clinical features and predictors of postoperative myocardial infarction (MI) after lung cancer surgery.Material and methods. The retrospective analysis included 2051 patients (1373 males and 678 females, mean age, 65,5 [62-69] years), who underwent thoracotomy for non-small cell lung cancer. At the first stage, the incidence rate of postoperative MI (%) was calculated with 95% confidential interval (CI) in relation to sex, age and extent of surgery. At the second stage, the case-control study was carried out in groups with MI revealed on the first stage (n=33) and without MI (n=130), formed by individual criteria-based matching. A comparative intergroup analysis was performed and prognostic value of 60 clinical perioperative indicators was assessed by odds ratio (OR). The features associated with MI in the univariateregression model were introduced into multivariate stepwise logistic regression. Independent MI predictors was revealed.Results. The postoperative IM incidence rate amounted to 1,61 [0,67-1,76]%. MI was more frequently diagnosed in men than women (0,29%), and after pneumonectomy (3,92%) compared with less operative extent (0,37%). MI was associated with comorbidities, smoking intensity, right pneumonectomy, preoperative increase in white blood cells, neutrophils and monocytes, blood loss volume, surgery duration, postoperative heart rate, preoperative decrease in serum total protein, postoperative haemoglobin, haematocrit, red blood cells decrease, and intraoperative blood pressure (BP). By means of multivariate logistic regression, the following factors with most accurate MI prediction were established: postoperative heart rate (OR, 4,06 [95% CI 1,58-10,43]), Sokolow-Lyon index (OR, 1,54 [95% CI 1,14-2,07]), ACS-NSQIP value for cardiac complications (OR, 3,86 [95% CI 1,36-10,92]), preoperative serum total protein (OR, 0,17 [95% CI 0,040,71]) and white blood cells (CR 1,54 [95% CI 1,03-2,31]), minimal intraoperative systolic BP (OR, 0,35 [95% CI 0,15-0,83]).Conclusion. Postoperative MI incidence in lung cancer patients accounts for 1,61%. Following independent predictors for postoperative MI were established: Sokolow-Lyon index, preoperative serum total protein and leukocytes levels, ACS-NSQIP value, minimal intraoperative systolic BP and postoperative heart rate.